The impact of endometrial preparation for frozen embryo transfer on maternal and neonatal outcomes: a review - Jacqueline C. Lee; Martina L. Badell; Jennifer F. Kawwass (BMC, 2022)
Abstract The use of frozen embryo transfer in assisted reproductive technology (ART) has steadily increased since development in the early 1980's. While there are many benefits to delayed frozen embryo transfer, certain adverse perinatal outcomes are noted to be more common in these transfers when compared to fresh transfers, specifically hypertensive disorders of pregnancy. Frozen embryo transfers require coordination between the embryo's developmental stage and the endometrial environment and can occur in either ovulatory or programmed cycles. Though there is no consensus on the ideal method of endometrial preparation prior to frozen embryo transfer, emerging data suggests differences in maternal and neonatal outcomes, specifically increased rates of hypertensive disorders of pregnancy in programmed cycles. Other reported differences include an increased risk of cesarean delivery, placenta accreta, postpartum hemorrhage, low birthweight, preterm birth, post term delivery, macrosomia, large for gestational age, and premature rupture of membranes in programmed cycles. The mechanism by which these differences exist could reflect inherent differences in groups selected for each type of endometrial preparation, the role of super physiologic hormone environments in programmed cycles, or the unique contributions of the corpus luteum in ovulatory cycles that are not present in programmed cycles. Given that existing studies are largely retrospective and have several key limitations, further investigation is needed. Confirmation of these findings has implications for current practice patterns and could enhance understanding of the mechanisms behind important adverse perinatal outcomes in those pursuing assisted reproduction.